Prevalence of Toxoplasma gondii indirect fluorescent antibodies in naturally- and experimentally-infected chickens (Gallus domesticus ) in Thailand. - Kamlang Chumpolbanchorn (2015)
Toxoplasma gondii infections in free-range (FR) chickens (Gallus domesticus)are potential public health risks. Antibodies for T. gondii were found in 194 out of 303 serum samples (64.03%) from FR chickens in Thailand tested by the indirect fluorescent antibody test (IFAT, 1:16). To verify the validity of serologic data in this survey, sera from chickens experimentally infected with the RH strain of T. gondii were tested by the IFAT. Antibodies against T. gondii were detected as early as 7 days p.i., peaked at 2 weeks, and then declined by 10 weeks p.i.